Estimates of Long-Term Disability Among US Service Members With Traumatic Brain Injuries. Issue 1 (January 2021) - Agimi, Yll; Marion, Donald; Schwab, Karen; Stout, Katharine
Abstract : Background: Traumatic brain injury (TBI) is a significant health issue in the US military. The purpose of this study was to estimate the probability of long-term disability among hospitalized service members (SMs) with TBIs, using the South Carolina Traumatic Brain Injury and Follow-up Registry (SCTBIFR) model developed on civilian hospitalized patients. Methods: We identified military patients in military or civilian hospitals or theater level 3 to 5 military treatment facilities (MTFs) whose first TBI occurred between October 1, 2013, and September 30, 2015. TBI-related disability at 1-year post–hospital discharge was estimated using regression coefficients from the SCTBIFR. Results: Among the identified 4877 SMs, an estimated 65.6% of SMs with severe TBI, 56.2% with penetrating TBI, 31.4% with moderate TBI, and 12.0% with mild TBI are predicted to develop long-term disability. TBI patients identified at theater level 4 and 5 MTFs had an average long-term disability rate of 56.9% and 61.1%, respectively. In total, we estimate that 25.2% of all SMs hospitalized with TBI will develop long-term disability. Conclusion: Applying SCTBIFR long-term probability estimates to US SMs with TBIs provides useful disability estimates to inform providers and health systems on the likelihood that particular subgroups of TBI patients will require continued support and long-term care. Abstract : Supplemental Digital Content is Available in the Text.